Perilaku Hidup Sehat Masyarakat Desa Siulak Kecil Mudik dalam Upaya Pencegahan Penularan Virus Corona - Eline Yanty Putri Nasution; Prita Kartika (Jurnal Pemberdayaan Masyarakat, 2022)
This cervice aims to determine the healthy lifestiles of Siulak Kecil Mudik Village community in order to prevent the Covid-19 Virus transmission. The method that used in this service was descriptive method. The target of this service are 10 village people that choosen with use purposive technique. According to the reflection of service programme result obtain the conclusion are: (1) Covid-19 pandemic cause the decrease of public health and income; (2) most of public in Siulak Kecil Mudik Village ignore the healthy lifestyles, and (3) the level of healthy lifestyles people is in low category. The steps which we done about the lowerness of the public healthy lifestyles are: (1) give the education abou the importance of the healty lifestyles; (2) collaborate with the village administrator about the implementation the healthy protocol;(3)inform the information about the importance of Â vaccination and confirmation about hoax report about the vaccination tha spread through the public.